Edukasi Mengenai Keaslian Uang Rupiah Di Kawasan Wisata Gunung Bromo - Swadia Gandhi Mahardika; Akbar Lufi Zulfikar; Sugiarto; Abiyajid Bustami (AMMA : Jurnal Pengabdian Masyarakat, 2024)
As a symbol of state sovereignty, the Indonesian people must respect and be proud of the rupiah as a legal means of payment. The aim of this outreach is to provide business actors in the Mount Bromo tourist area with in-depth knowledge and understanding of the true characteristics of rupiah currency. This activity was carried out in the Mount Bromo tourist area in East Java. Business actors responded positively to the socialization of the characteristics of real money and fake money. Business people's knowledge and awareness of how to distinguish real money from fake has increased as a result of the outreach campaign. It is hoped that this will help prevent the spread of counterfeit money in society, including in the Mount Bromo tourist area.